Translation and Circulation of Hoffmann’s Works in Mexico (1840-1910) - Hernández Roura, Sergio Armando (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
Based on the translations, articles, announcements, notes and mentions dedicated to E.T.A Hoffmann appeared in the Mexican press, the reconstruction of the process of translation and circulation of the work of the German author in Mexico is presented. In this aspect of the phenomenon of reception it is possible to appreciate the change of horizon that took place in Mexican society about the work of the analyzed author as well as in terms of the circulation of German works during the 19th century and the first years of the 20th.